Measuring the shower maximum of extensive air showers using imaging atmospheric Cherenkov telescopes - Giler, Andres Gabriel Delgado (2019)
Cosmic rays are at the foundation of astroparticle physics and the extensive air showers (EAS) is one indirect way to detect them. Air showers, however, have been used to infer information not just of cosmic rays particles, but also to localize gamma rays sources. The shower maximum of an EAS, defined as the position at the atmosphere where the maximum quantity of charged particles is reached, is an observable of air showers that can permit to infer the mass composition of cosmic rays. For this reason, it is important to propose methods to measure it. Several methods to determine the shower maximum have been implemented in the last decades with the development of different kinds of telescopes. This work discusses the possibility of determining the maximum of air showers using imaging atmospheric Cherenkov telescopes (IACT). The Cherenkov telescopes can detect the Cherenkov radiation produced by the interaction of charged particles with the atmosphere. Those Cherenkov photons are projected back into the plane containing the longitudinal development of the air shower. Each plane is saved as a 2D histogram with the longitudinal and lateral development in the vertical and horizontal axis, respectively. A detailed analysis of each 2D histogram is presented and used to obtain the depth of the maximum of the Cherenkov profile. The main effect seen is a decrease in the shower maximum of Cherenkov photons as a function of the telescope position from the shower axis to 150 m. After 150m from the shower axis, there is a constant behavior that is correlated to the real depth of the maximum of an EAS. Based on this constant behavior after 150 m, the shower maximum is reconstructed and it is shown the resolution of the method as a function of the energy, which is around 55 g/cm2 considering just one telescope, and 15 g/cm2 for the best case considering zenith angle of 20 degrees. Moreover, the method is tested with some simulations took from Very Energetic Radiation Imaging Telescope Array System (VERITAS) experiment to compare with the results of our simulations. The resolution of the reconstruction of the shower maximum for proton and iron showers was also done which ranges around 80 g/cm2 for proton and around 30 g/cm2 for iron in the case of 20° of zenith angle.